2008
DOI: 10.1002/adfm.200800363
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Size‐Selective Bioseparation of Magnetic Silica Nanospheres with Highly Ordered Periodic Mesostructure

Abstract: In this paper, we report a novel synthesis and selective bioseparation of the composite of Fe3O4 magnetic nanocrystals and highly ordered MCM‐41 type periodic mesoporous silica nanospheres. Monodisperse superparamagnetic Fe3O4 nanocrystals were synthesized by thermal decomposition of iron stearate in diol in an autoclave at low temperature. The synthesized nanocrystals were encapsulated in mesoporous silica nanospheres through the packing and self‐assembly of composite nanocrystal–surfactant micelles and surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(127 citation statements)
references
References 58 publications
(80 reference statements)
2
124
0
Order By: Relevance
“…The C1s peak observed in the FDU-12 pure silica spectrum can most probably be attributed to residual surfactant. Figure 5 displays the solid state 13 C-CP-MAS NMR spectra of the various organo-functionalized FDU-12 samples. The three peaks in Figure 5A at the chemical shifts 8.4, 25.2, and 40.7 ppm can be attributed to the carbon atoms C 1 , C 2 , and C 3 , respectively, of the aminopropyl group that is incorporated into the silica framework (Si-O-Si-C 1 -C 2 -C 3 -NH 2 ) by cocondensation of APTES and TEOS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The C1s peak observed in the FDU-12 pure silica spectrum can most probably be attributed to residual surfactant. Figure 5 displays the solid state 13 C-CP-MAS NMR spectra of the various organo-functionalized FDU-12 samples. The three peaks in Figure 5A at the chemical shifts 8.4, 25.2, and 40.7 ppm can be attributed to the carbon atoms C 1 , C 2 , and C 3 , respectively, of the aminopropyl group that is incorporated into the silica framework (Si-O-Si-C 1 -C 2 -C 3 -NH 2 ) by cocondensation of APTES and TEOS.…”
Section: Resultsmentioning
confidence: 99%
“…13 C solid state cross-polarization magic-angle spinning nuclear magnetic resonance ( 13 C-CP-MAS NMR) measurements were performed on a Bruker MSL-300 spectrometer operating at a frequency of 75.482 MHz for 13 C. The spectrometer was equipped with a 4 mm double air bearing, magic-angle spinning probe suitable for MAS experiments. The proton 90°pulse time was 5.5 µs, the acquisition time was 45 ms, the cross-polarization time was 2 ms, and the relaxation delay was 3 s. The spectrum width was 50 kHz, and 4000 data points were collected over 2000 scans.…”
Section: Synthesis Of Nonfunctionalized Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al have recently synthesized composites of Fe 3 O 4 magnetic nanocrystals and MCM-41 type periodic mesoporous silica nanospheres, and demonstrated that the mesoporous magnetic nanospheres can be used to separate cytochrome c from binary cytochrome c and bovine serum albumin solution. 15 He et al have explored two kinds of silica coated magnetic NPs as pH-dependent magnetic nanoadsorbents for the selective separation of proteins. 16 Lin et al reported synthesis of aminophenylboronic acid-functionalized magnetic iron oxide NPs for the selective capture of glycoproteins from unfractionated protein mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a main merit of these TiO 2 membranes is their photocatalytic activity, which is able to effective declogging of these membranes when applied to separate proteins. Mesoporous silica coated carbon nanotubes [72], mesoporous polymer coated copper hydroxide nanostrands [73], magnetic silica nanospheres with highly ordered periodic mesostructure [74] and lysozyme imprinted polymer beads [75] are also synthesized for the selective separation of proteins with different molecular sizes.…”
Section: Size-selective Enrichment Of Endogenous Peptides and Proteinsmentioning
confidence: 99%